Role of Meddra and Oracle Argus Safety in Clinical Data Management and Pharmacovigilance - Deshmane Bhagyashree Pravin; Pawar Suchita; Lavate Shivani; Mane Pranjali; Ovhal Prabhakar; Sonwalkar Priyanka (Asian Journal of Pharmaceutical Research and Development, 2026)
Pharmacovigilance and clinical data management are critical components of drug safety and regulatory compliance throughout the drug development lifecycle. The MedDRA (Medical Dictionary for Regulatory Activities) and Oracle Argus Safety play a vital role in standardizing, processing, and evaluating safety data. MedDRA provides a globally accepted, standardized medical terminology that facilitates accurate coding, classification, and analysis of adverse events, ensuring consistency in regulatory reporting across different regions. Oracle ArgusSafety, a comprehensive pharmacovigilance database system, enables efficient case processing, signal detection, and regulatory reporting. It integrates MedDRA for precise adverse event coding and supports compliance with international regulatory requirements such as those from the FDA and EMA. Together, these tools enhance data quality, improve workflow efficiency, and enable timely detection of potential safety signals. In clinical data management, the integration of MedDRA and Argus Safety ensures structured data collection, uniform terminology usage, and reliable safety evaluation. This combination supports better decision-making, risk assessment, and ultimately contributes to patient safety. The adoption of these systems represents a significant advancement in modern pharmacovigilance practices, promoting global harmonization and regulatory transparency.